2017
DOI: 10.1093/neuonc/now309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the significance of density, localization, and PD-1/PD-L1 immunopositivity of mononuclear cells in the clinical course of lung adenocarcinoma patients with brain metastasis

Abstract: This is the first study demonstrating the independent prognostic value of mononuclear rings in LUAD cases with brain metastasis. Our results also suggest that the density of tumor-associated ICs in addition to PD-L1 expression of tumor cells and ICs as well as PD-1 expression of ICs may hold relevant information for the appropriate selection of patients who might benefit from anti-PD-L1 or anti-PD-1 therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 51 publications
2
26
1
1
Order By: Relevance
“…The brain TME was found to have lost PD-1 + TILs despite their presence in primary lung cancer specimens, which is a novel finding of this study. In accordance with others [31–33], adenocarcinoma patients displayed a more distinctive pattern of a low infiltration of both CD3 + and CD8 + TILs, suggesting that a significant number of patients lack any significant local immune response in association with their BM. Although PD-L1 expression of tumor cells showed no significant differences in this study, others have reported that BM lost PD-L1 expression that was normally present in primary lung cancer specimens [22, 34].…”
Section: Discussionsupporting
confidence: 91%
“…The brain TME was found to have lost PD-1 + TILs despite their presence in primary lung cancer specimens, which is a novel finding of this study. In accordance with others [31–33], adenocarcinoma patients displayed a more distinctive pattern of a low infiltration of both CD3 + and CD8 + TILs, suggesting that a significant number of patients lack any significant local immune response in association with their BM. Although PD-L1 expression of tumor cells showed no significant differences in this study, others have reported that BM lost PD-L1 expression that was normally present in primary lung cancer specimens [22, 34].…”
Section: Discussionsupporting
confidence: 91%
“…High PD-L1 expression has been associated with longer OS in pMMR mCRC in some studies, but not all [31]. In addition, in lung cancer with BM, PD-L1 expression has been associated with worse OS [32]. Our study highlighted two other prognostic markers, single BM and the absence of lung metastases that had already been reported for patients with BM whatever the primary tumor.…”
Section: Discussionsupporting
confidence: 68%
“…Lung adenocarcinoma (LAD), the most common subtype of non-small-cell lung cancer (NSCLC) which accounts for the majority of all primary lung cancer cases diagnosed, has a low 5-year survival rate [2,3]. In the past decades, we have made great improvements in the treatment of NSCLC, such as anti-PD-1/PD-L1 therapy [4,5], targetted therapies [6,7], which are also suitable for LAD treatment [8,9]. Meanwhile, the therapeutic strategies for treating LAD also improved [10–12].…”
Section: Introductionmentioning
confidence: 99%